Interactive Visualization of Hand, Foot & Mouth Diseases (HFMD) - Azlan, Aiman (IRC, 2019)
This paper describes the concepts and method for Interactive Visualization of Hand, Foot and Mouth Diseases for Public Awareness. This system will be created on a webbased application platform based on the data visualization system. The primary goal of this project is to help decision makers to make better decisions regarding Hand, Foot and Mouth Disease with visualized data which allows people to quickly capture large amounts of data illustrated in different formats. While indirectly enabling faster decision-making process, decision makers can plan their actions based on real trends and patterns. The issue with the present condition is that no current applications focuses on reducing HFMD from occurring and assist decision makers (health practitioners and institutions) to make decisions in planning their strategies and action. For the project, the scope focuses on HFMD and Malaysia. Waterfall SDLC model is implemented for the project innovations and will be explained in one of this paper's sections. In this article there will be five chapters: introduction, literature review, methodology, result and discussion, and finally, conclusion and recommendation of the Interactive Visualization of Hand, Foot and Mouth Diseases for Public Awareness.